ChemInform Abstract: Catalytic Properties of Unsupported Palladium Nanoparticle Surfaces Capped with Small Organic Ligands. Issue 23 (June 2015) - Gavia, Diego J.; Shon, Young‐Seok
Abstract Review: 105 refs.